PENGELOLAAN TANAH WAKAF MASJID DI KOTA MANADO - Salim Hasan; Ahmad Rajafi (Aqlam: Journal of Islam and Plurality, 2018)
Abstract. This article will specifically examine the elements related to the management of Mosque Waqf Land, Manado City, whether it has been functioning as the act or whether the law has not been able to accommodate the problems that occur in the management of waqf land in Manado City. The result is that the management of waqf land in Manado City is classified into two things, namely effective and ineffective. But ineffective is more than effective, this is because many mosque administrators feel that the process of obtaining certificates is very procedural, so they have difficulty managing the certificate. So that, the relavancy is with the enactment of Law Number 41 year 2004 concerning Waqf, the recording of legal waqf acts is obligatory to provide legal protection and legal certainty for wakif, Nazhir and that assets that are represented.Keywords: Management, Mosque Waqf Land, Manado City, Law Number 41 year 2004Abstrak. Artikel ini secara spesifik akan menelaah tentang unsur-unsur yang terkait dalam  pengelolaan wakaf tanah masjid di Kota Manado, apakah sudah berfungsi sebagaimana UU tersebut ataukah UU tersebut belum dapat mengakomodir permasalahan-permasalahan yang terjadi dalam pengelolaan wakaf tanah masjid di Kota Manado. Hasilnya adalah, bahwa pengelolaan wakaf tanah masjid di Kota Manado terklasifikasi pada dua hal, yakni efektif dan tidak efektif. Namun yang tidak efektif lebih banyak dari yang efektif, hal ini disebabkan karena banyak pengurus masjid merasa bahwa proses pengurusan sertifikat sangat prosedural, sehingga mereka kesulitan untuk mengurus sertifikat tersebut. Relevenasinya adalah, dengan berlakunya UU No. 41 Tahun 2004 tentang Wakaf, maka pencatatan perbuatan hukum wakaf menjadi wajib hukumnya untuk memberikan perlindungan hukum dan kepastian hukum bagi wakif, Nazhir serta harta yang diwakafkan.Kata Kunci: Pengelolaan, Tanah Wakaf Masjid, Kota Manado, UU No. 41 Tahun 2004